2014
DOI: 10.1136/sextrans-2013-051336
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of prevention of mother-to-child-transmission using Option B+ in northern rural Malawi: a retrospective cohort study

Abstract: To identify points of dropout on the pathway from offering HIV testing to maintenance on antiretroviral therapy (ART), following the introduction of the Option B+ policy for pregnant women in Malawi (lifelong ART for HIV-positive mothers and 6 weeks nevirapine for the infants), a retrospective cohort study within a demographic surveillance system in northern Malawi. Women living in the demographic surveillance system who initiated antenatal care (ANC) between July 2011 (date of policy change) and January 2013,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 17 publications
(17 reference statements)
3
36
1
Order By: Relevance
“…Modeling data suggest the cost-effectiveness of the Option B+ strategy, but the benefits are lost if the risk of HIV-1 RNA failure increases by even 2.4% [26]. Early data from Malawi (the first country to adopt option B+) do not report on adherence or viral suppression, but about half of women eligible for ART did not initiate treatment [27] and 27% of women who initiated therapy were lost to follow-up at one year [9]. Roll-out of Option B+ is happening very quickly and is planned or considered for many sub-Saharan African countries[28].…”
Section: Discussionmentioning
confidence: 99%
“…Modeling data suggest the cost-effectiveness of the Option B+ strategy, but the benefits are lost if the risk of HIV-1 RNA failure increases by even 2.4% [26]. Early data from Malawi (the first country to adopt option B+) do not report on adherence or viral suppression, but about half of women eligible for ART did not initiate treatment [27] and 27% of women who initiated therapy were lost to follow-up at one year [9]. Roll-out of Option B+ is happening very quickly and is planned or considered for many sub-Saharan African countries[28].…”
Section: Discussionmentioning
confidence: 99%
“…Existing early literature has shown that barriers to successful implementation throughout the cascade of Option B+ services may affect the uptake and adherence to ART by pregnant women, the follow-up of HIV-exposed infants and the long-term retention of this patient population [3,4]. Considerable variation in retention on ART of Option B+ women exists between health facilities [4].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable variation in retention on ART of Option B+ women exists between health facilities [4]. Urgent research priorities at the national level with the Malawi Ministry of Health (MOH) have been identified that include evaluation of barriers and facilitators to uptake of lifelong ART and long-term retention by largely asymptomatic and newly diagnosed HIV-positive women seeking antenatal care (ANC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Having skated over the surface of these papers, I will draw your attention to an equally fascinating range of articles on topics ranging from prevention of mother to child transmission of HIV,11 Human papillomavirus vaccination in women attending English sexual health clinics,12 partnership factors affecting the use of condoms in heterosexuals;13 the sexual health of female sex workers,14 estimation of sexual mixing15 and HPV viral load and persistence in HIV positive men 16…”
mentioning
confidence: 99%